Influência da auto seleção à luz no ritmo circadiano de atividade motora em Callithrix Jacchus - Gonçalves, Fabiana Barbosa (2006)
Marmosets, Callithrix jacchus, are strictly diurnal animals. The motor activity rhythmicity is generated by the circadian timing system and is modulated by environmental factors, mainly by photic stimuli that compose the light-dark cycle. Photic stimuli can reset the biological oscilators changing activity motor pattern, by a mechanism called entrainment. Otherwise, light can act directly on expressed rhythm, without act on the biological oscillators, promoting the masking. Thus, photic stimuli can synchronize the circadian activity rhythm (CAR) by two distinct mechanisms, acting isolated or at a combined way. Among the elements that can influence photic synchronization, the duration and time of photic exposure is pointed out. If in the natural environment the marmoset can choose places of different intensity illumination and is synchronized to light-dark cycle (LD), how the photic synchronization mechanism can be evaluated in laboratory by light self-selection? With objective to response this question, four adult male marmosets were studied at two conditions: with and without sleeping box. The animals were submitted to a LD cycle (12:12/ 350:2 lx) and constant light (LL: 350 lx) conditions in individual cages with an opaque sleeping box, that permitted the light self-selection. At the room, the temperature was 25.6 ºC (± 0.3 ºC) and humidity was 78.7 (± 5%). The motor activity was recorded at 5 min bins by infrared movement sensors installed at the top of the cages. The motor activity profile was distinct at the two conditions: without the sleeping box protection against light, the activity frequency was higher at CT 11-12 (ANOVA; F(3.23) = 62.27; p < 0.01). Also, the duration of the active phase (α) was prolonged of about 1 h (t test, p < 0.05) and the animals showed a significant delay on the activity onset and offset (t test, p < 0.05) and at the acrophase (confidence intervals of 5%) of CAR. In LL, the light continuous exposure prolonged the active phase and influenced the endogenous expression of the circadian activity rhythm period. From the result analysis, it is concluded that the light self-selection can modify several parameters of CAR in marmosets, allowing the study of the synchronization mechanism using the burrow model. Thus, without sleeping box there was a phase delay between the CAR and LD (entrainment) and an increase of activity near lights off (positive masking). Furthermore, in LL, the light continuous exposure modifies α and the endogenous expression of CAR. It is suggested that the light self-selection might be take into account at investigations that evaluate the biological rhythmicity in marmosets